Mitochondrial function, grip strength, and activity are related to recovery of mobility after a total knee arthroplasty. Issue 2 (19th November 2022) - van Diemen, Marcus P. J.; Ziagkos, Dimitrios; Kruizinga, Matthijs D.; Bénard, Menno R.; Lambrechtse, Philip; Jansen, Joris A. J.; Snoeker, Barbara A. M.; Gademan, Maaike G. J.; Cohen, Adam F.; Nelissen, Rob G. H. H.; Groeneveld, Geert Jan
Abstract: Low muscle quality and a sedentary lifestyle are indicators for a slow recovery after a total knee arthroplasty (TKA). Mitochondrial function is an important part of muscle quality and a key driver of sarcopenia. However, it is not known whether it relates to recovery. In this pilot study, we monitored activity after TKA using a wrist mounted activity tracker and assessed the relation of mitochondrial function on the rate of recovery after TKA. Additionally, we compared the increase in activity as a way to measure recovery to traditional outcome measures. Patients were studied 2 weeks before TKA and up to 6 months after. Activity was monitored continuously. Baseline mitochondrial function (citrate synthase and complex [CP] 1–5 abundance of the electron transport chain) was determined on muscle tissue taken during TKA. Traditional outcome measures (Knee Injury and Osteoarthritis Outcome Score [KOOS], timed up‐and‐go [TUG] completion time, grip, and quadriceps strength) were performed 2 weeks before, 6 weeks after, and 6 months after TKA. Using a multivariate regression model with various clinical baseline parameters, the following were significantly related to recovery: CP5 abundance, grip strength, and activity (regression weights 0.13, 0.02, and 2.89, respectively). During recovery, activity correlated to the KOOS‐activities of daily living (ADL) score ( r  = 0.55, p  = 0.009) and TUG completion time ( r  = −0.61, p  = 0.001). Mitochondrial function seems to be related to recovery, but so are activity and grip strength, all indicators of sarcopenia. Using activity trackers before and after TKA might give the surgeon valuable information on the expected recovery and the opportunity to intervene if recovery is low.